Effect of Alkaloids Extracts From Solanum nigrum L.(Solanaceae) in DNA -Plasmid PBR322 by Using Gel Electrophoresis - Fayidh, M.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Four  alkaloids  compounds  were  extracted  from  the  fruits  and leaves, of plant known locally as (Anab AI-Thebe Solanum nigram), by various solvents systems, from an earlier study by the researcher. DNA tested its effect in plasmid PBR322 deportation  method using Gel Electrophoresis. Results showed that two of those extract for full effectiveness   digestible   pieces  of  RNA and  DNA  plasmid,   and digestive  partly  of  the  other  alternatives.  That  could  prove  results indicate that this type of alkaloids consist of   biological effectiveness of anti-twnors, through DNA digestion spare low molecular weight, as well as their effectiveness as antibacterial which   had been found previously.